Analysis of Factors Which Affect Budgetary Slack (Survey of SOE in Bandung) - Melania Lintang Kenisah; Yenni Carolina; Rapina Rapina (KINERJA, 2020)
This study aims to analyze the factors that affect budgetary slack which include employee motivation and asymmetric information with participative budgeting as the antecedent variables. The research method was conducted through a survey method by distributing questionnaires to 229 heads of responsibility center on SOEs in Bandung. In addition, interviews and group discussions were conducted to improve data collection. The data obtained were analyzed using the structural equation model - LISREL. The results showed that asymmetric information has a positive effect on budgetary slack and employee motivation has a negative effect on budgetary slack. Meanwhile, participative budgeting has a positive effect on asymmetric information and employee motivation.Keywords: Participative Budgeting, Asymmetric Information, Employee Motivation, Budgetary Slack